Current Situation and Countermeasures of Singing Teaching in Universities - Ma, Heting (International Journal of Global Economics and Management, 2024)
The purpose of this paper is to discuss the current situation and existing problems of university singing teaching in China, and to put forward corresponding countermeasures and suggestions. Firstly, the introduction part explains the significance and value of university singing teaching, and briefly introduces the purpose and method of the study. Then, through the analysis of the current situation of university singing teaching, it is found that there are problems such as single teaching mode, insufficient teachers and quality problems, low student participation and insufficient curriculum resources. On this basis, this paper puts forward corresponding countermeasures and suggestions in terms of reforming the teaching mode and method, strengthening the construction of teaching staff, improving students’ participation, and optimising the curriculum and teaching materials.